2023
DOI: 10.1177/87552930231170894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the optimal ground motion intensity measure in the prediction of the seismic vulnerability of earth dams

Abstract: The large majority of existing earth dams were designed with old standards, which often accounted for the effects of earthquakes in a simplified manner. As a result, seismic re-evaluation of these structures is now becoming increasingly important for dam owners. The seismic performance of earth dams can be evaluated at different levels of resolution, typically ranging from simple sliding block analysis, to the use of advanced numerical models. Seismic inputs for these models are typically chosen using code-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…As an example, using either field data, relative to postseismic surveys, or numerical predictions, obtained through advanced finite difference or finite element analyses, relative to different types of earth dams, several studies showed the relationship between the permanent crest settlement and the peak ground acceleration or velocity (e.g., Lanzo et al, 6 Lanzo, 7 Park et al, 8 Ghaemi and Konrad, 4 Armstrong et al, 9 Regina et al 10 ), the Arias Intensity (e.g., Yule et al, 11 Sica and Pagano 5 , Brigante and Sica, 12 Pagano and Sica, 13 Lanzo et al, 6 Lanzo, 7 Park et al, 8 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ), the cumulative absolute velocity (i.e. the integral of the acceleration time-history, e.g., Lanzo et al, 6 Armstrong et al, 9 Regina et al 10 ), the bracketed (e.g., Yule et al, 11 for a threshold acceleration equal to 0.05 g) or the strong motion (Lanzo et al, 6 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ) duration, the specific energy density (i.e., the integral of the squared velocity time-history; e.g., Lanzo et al 6 ), the destructiveness potential factor (e.g., Cascone et al 14 ), the mean or the predominant period (e.g., Lanzo et al, 6 Ghaemi and Konrad 4 ) and, finally, the pseudo spectral acceleration computed for different vibration periods (e.g., Armstrong et al, 9 Regina et al 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As an example, using either field data, relative to postseismic surveys, or numerical predictions, obtained through advanced finite difference or finite element analyses, relative to different types of earth dams, several studies showed the relationship between the permanent crest settlement and the peak ground acceleration or velocity (e.g., Lanzo et al, 6 Lanzo, 7 Park et al, 8 Ghaemi and Konrad, 4 Armstrong et al, 9 Regina et al 10 ), the Arias Intensity (e.g., Yule et al, 11 Sica and Pagano 5 , Brigante and Sica, 12 Pagano and Sica, 13 Lanzo et al, 6 Lanzo, 7 Park et al, 8 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ), the cumulative absolute velocity (i.e. the integral of the acceleration time-history, e.g., Lanzo et al, 6 Armstrong et al, 9 Regina et al 10 ), the bracketed (e.g., Yule et al, 11 for a threshold acceleration equal to 0.05 g) or the strong motion (Lanzo et al, 6 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ) duration, the specific energy density (i.e., the integral of the squared velocity time-history; e.g., Lanzo et al 6 ), the destructiveness potential factor (e.g., Cascone et al 14 ), the mean or the predominant period (e.g., Lanzo et al, 6 Ghaemi and Konrad 4 ) and, finally, the pseudo spectral acceleration computed for different vibration periods (e.g., Armstrong et al, 9 Regina et al 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, using either field data, relative to postseismic surveys, or numerical predictions, obtained through advanced finite difference or finite element analyses, relative to different types of earth dams, several studies showed the relationship between the permanent crest settlement and the peak ground acceleration or velocity (e.g., Lanzo et al., 6 Lanzo, 7 Park et al., 8 Ghaemi and Konrad, 4 Armstrong et al., 9 Regina et al 10 11 Sica and Pagano 5 , Brigante and Sica, 12 Pagano and Sica, 13 Lanzo et al., 6 Lanzo, 7 Park et al., 8 Armstrong et al., 9 Cascone et al., 14 Regina et al 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have been conducted on the uncertainty analysis of different IMs in predicting damage levels. Regina et al [4], found that the CAV is the optimal IM in predicting the vulnerability of earth dams and the fragility functions based on the CAV have the lowest standard deviation values. Armstrong et al [5], found that the AI was the most efficient IM, however, the CAV has the lower total standard deviation in the evaluation of earth dams.…”
Section: Introductionmentioning
confidence: 99%